Glória e tragédia: a dualidade da prestação de contas do Sport Club Corinthians Paulista em seus relatórios de sustentabilidade - Brondani, Roberta Ferreira [UNESP] (2015)
This paper aims to analyze how the Sport Club Corinthians Paulista, tradicional sports club founded in 1910 in São Paulo (SP), has shown its accountability and transparency in its Sustainability Reports published since 2009. The study aims to verify Corinthians's intentions in publishing such reports, in views that this is a profit organizations' practice, especially companies with shares on Stock Exchange (such as Corporations - S/A), and something unusual among sports associations. The hypothesis is that Corinthians leverages the credibility of sustainability reports to sell the image of a modern enterprise, organized, transparent and socially reponsible, emphasizing good points even when the facts show the opposite, in addition to using them as part of disclosure to attract new sponsors and investors. Therefore, the analysis corpus are from 2012 and 2013. Sustainability Report, years that market the history of the club due to facts that are opposed by his extraordinary character. The 2012 year was market by unprecedented glory, as victories in the Libertadores Cup and FIFA Club World Championship in its new format. However the year 2013 was evidenced by unexpected tragedies, like the death of a Bolivian fans during the match in Libertadores Cup and accidents involving workers in the construction of the new stadium of Corinthians, which would be used as one of the 2014 World Cup stage in Brazil. To verify that there was balance among publications were used as methodology Content Analysis and the GRI principles - Global Reporting Initiative, which define parameters to ensure the content and quality of the report, specifically the Balance Principle